Effective GPS jamming techniques for UAVs using low-cost SDR platforms - Ferreira, R. (2020)
Lately, a rising number of incidents between unmanned aerial vehicles (UAVs) and airplanes have been reported in airports and airfields. In order to help cope with the problem of unauthorized UAV operations, in this paper we evaluate the use of low cost SDR platforms (software defined radio) for the implementation of a jammer able to generate an effective interfering signal aimed at the GPS navigation system. Using a programmable BladeRF x40 platform from Nuand and the GNU radio software development toolkit, several interference techniques were studied and evaluated, considering the spectral efficiency, energy efficiency and complexity. It was shown that the tested approaches are capable of stopping the reliable reception of the radionavigation signal in real-life scenarios, neutralizing the capacity for autonomous operation of the vehicle.